The GCF is 3.
((15xy2)/(x2+5x+6))/((5x2y)/(2x2+7x+3)) =(15xy2/5x2y)*(2x2+7x+3)/(x2+5x+6) =(3y/x)*(((2x+1)(x+3))/((x+2)(x+3) =(3y(2x+1))/(x(x+2)) =(6xy+3y)/(x2+2x)
3x + 7y
3xy + 3y2 = 3y (x + y)
If you mean 3x+2y = -5 and -2x+3y = -5 then they are straight line equations
(3x + 3y)(x + y) = 3(x + y)2
2x2 + 6xy = 2x (x + 3y)
(3x + 3y)(x + y) or 3(x + y)2
(a + x - 3y)(a - x + 3y)
3y2 - 2y + 6xy - 4x = y(3y - 2) + 2x(3y - 2) = (y + 2x)*(3y - 2)
The expression 3x + 3y is a linear combination of two variables, x and y, with coefficients 3. The answer to this expression depends on the specific values of x and y. If x = 2 and y = 4, then the answer would be 3(2) + 3(4) = 6 + 12 = 18. In general, the answer to 3x + 3y is 3 times the sum of x and y.
By factorisation: x2 + 6xy - 27y2 = (x + 9y)(x - 3y).
3y(3x - 2y)(9x^2 + 6xy + 4y^2)
If that's +6xy, the answer is 2x(x + 3y) If that's -6xy, the answer is 2x(x - 3y)
The GCF is 3.
0
3x + y